Unemployment in Interwar Germany: An Analysis of the Labor Market, 1927-1936. - Dimsdale, N; Horsewood, N; Riel, A (Cambridge University Press, 2006)
This article contributes to the debate on the causes of unemployment in interwar Germany. It applies the Layard-Nickell model of the labor market to interwar data. The results indicate that demand shocks, combined with nominal inertia in the labor market, were important in explaining unemployment. Real wage pressures due to procedures for wage determination were a major influence on unemployment, but were partly offset by movements in other supply-side variables, such as the replacement ratio and the pricing policy of cartels. Demand- and supply-side variables were mutually reinforcing in the Great Depression and in the recovery under the Nazis.